Behavior of European pear cultivars to floral bud necrosis in southern Brazil - Goncalves M.J.* (2014)
© 2014 Elsevier Ltd.The pear crop offers an expansive market opportunity in southern Brazil, because of suitable climatic conditions and available infrastructure. However, there are still some barriers that prevent satisfactory economic production. Floral bud necrosis (FBN) is one of the main problems afflicting pear orchards in southern Brazil. FBN is characterized by the occurrence of necrosis in the flower primordia of floral buds decreasing the crop yield potential. The objective of this work was to evaluate the behavior of European pear cultivars (Clapp's Favourite, Conference, Packham's Triumph, Rocha, Abate Fetel, Santa Maria, Decana and William's) grafted on quince rootstocks (Adams, EMA and EMC) to FBN susceptibility in two different phenological stages (vegetative dormancy and green tip) and two different edaphoclimatic regions (Fraiburgo/SC and Urupema/SC) of southern Brazil during the 2009/2010 and 2010/2011 growing seasons. Twenty floral buds at both phenological stages of vegetative dormancy and green tip were collected in 10 randomized plants per plot in each region. The floral buds were assessed by microscope following the symptomatic scale of: 1. Floral buds with absence of necrosis; 2. Floral buds with partial necrosis and, 3. Floral buds with total necrosis. The combinations Conference/Adams and Packham's Triumph/EMA and the combination Abate Fetel/Adams showed the highest severity of floral bud necrosis in both phenological stages evaluated in the region of Fraiburgo/SC and Urupema/SC, respectively. The Clapp's Favourite/EMA and Conference/EMC combinations significantly showed the lowest severity of FBN in both the phenological stages of vegetative dormancy and green tip in both regions of Fraiburgo/SC and Urupema/SC, in the edaphoclimatic conditions of southern Brazil during the 2009/2010 and 2010/2011 growing seasons.